The Role of Humans in Poultry Disease Outbreaks - Gary Butcher; Mojtaba Yegani (EDIS)
VM174, a 3-page fact sheet by Gary Butcher and Mojtaba Yegani, focuses on the roles people may play in the occurrence of diseases in commercial poultry operations and what should be done to reduce or minimize the effects of this potential risk factor. Published by the UF College of Veterinary Medicine, December 2008.